From Flesh to Text: The Chapters on the Uterus and Its Parts in Rodrigo de Castro’s De uniuersa mulierum medicina - Cristina Santos Pinheiro (Ágora, 2021)
The anatomy of the uterus and its constituent parts was an essential section in early modern medical treatises, both general texts and specialist texts in gynaecology and obstetrics. In this paper, I examine the section of Rodrigo de Castro’s De uniuersa mulierum medicina devoted to the subject (chapters 2 and 3 of Book 1, Part 1 “Theoria”), both as regards what he says about the anatomical characteristics of these parts and the controversies and questions of morality associated with the uterus.